The moderating role of extraversion in the relationship between trait mindfulness and pain adaptation - Lu, Chen; Berner, Nele; Hagel, Lena; Heukamp, Nils Jannik; Moliadze, Vera; Nees, Frauke (Frontiers in Pain Research, 2025)
IntroductionPain habituation, the reduction in response to repeated painful stimuli, is a positive adaptation process, while pain sensitization is linked to chronic pain. Traits like mindfulness and extraversion affect pain processing, but their influence on pain adaptation and potential interactions remains underexplored. This study aimed to examine the relationship between trait mindfulness, extraversion, and pain adaptation, assessing their predictive value and any interaction effects.Materials and methodFifty-two healthy participants, mean age = 23.29 ± 2.052 years, completed questionnaires measuring trait mindfulness and extraversion, followed by an experimental pain stimulation to assess pain adaptation. Correlation analysis and hierarchical regression analysis were used to explore the relationships between traits and pain adaptation, and potential interaction effects.ResultTrait mindfulness positively correlated with extraversion, but neither trait showed a significant correlation with pain adaptation. In addition, neither trait mindfulness nor extraversion significantly predicted pain adaptation. However, a significant interaction was found between the two traits, suggesting that extraversion moderates the relationship between trait mindfulness and pain adaptation.ConclusionTrait mindfulness and extraversion are interrelated traits whose interaction affects pain habituation and the extent to which individuals with higher levels of trait mindfulness exhibit greater pain adaptation appears to depend on their levels of extraversion. These findings suggest that trait mindfulness and extraversion may act as protective factors in chronic pain development. Mindfulness-based interventions may be particularly effective for individuals with specific personality traits. This can inform further research to explore these implications for pain management.